2021
DOI: 10.21203/rs.3.rs-575849/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial Community Analysis of Rhizosphere of Healthy and Wilted Pepper (Capsicum Annuum L.) in An Organic Farming System

Abstract: Rhizosphere microorganisms play an important role in the growth and health of plants. Around the world, diverse soil-borne pathogens attack Capsicum annuum causing significant damage and economic losses; however, very little is known about how rhizosphere microbial communities are altered by infestation with root pathogens. This work aimed to determine whether the diversity and structure of microbial communities in the rhizosphere soil of C. annuum plants is significantly changed by wilt disease. We used 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…6). In comparison, existing studies showed no differences in alpha diversity upon above [61] or Fig. 7 Variation in beta diversity of differently treated apple saplings at three distinct timepoints (TP) in the L-compartment (upper panel) and T-compartment (lower panel).…”
Section: Above Ground Pathogen Infection Causes Changes In the Root-a...mentioning
confidence: 80%
“…6). In comparison, existing studies showed no differences in alpha diversity upon above [61] or Fig. 7 Variation in beta diversity of differently treated apple saplings at three distinct timepoints (TP) in the L-compartment (upper panel) and T-compartment (lower panel).…”
Section: Above Ground Pathogen Infection Causes Changes In the Root-a...mentioning
confidence: 80%